Terbium-doped ZnS quantum dots: Structural, morphological, optical, photoluminescence, and photocatalytic properties. Issue 10 (July 2018) - Poornaprakash, B.; Chalapathi, U.; Suh, Youngsuk; Vattikuti, S.V. Prabhakar; Reddy, M. Siva Pratap; Park, Si-Hyun
Abstract: Terbium (0, 2, and 4 at%)-doped ZnS quantum dots (QDs) were synthesized via a solvothermal method. The crystal structures of the synthesized QDs were determined to be zinc blend by X-ray powder diffraction (XRD) and Raman analyses. Transmission electron microscopy (TEM) studies revealed that particles with a mean size of 2–4 nm were formed. An X-ray photo electron spectroscopy (XPS) examination disclosed the existence of terbium with a trivalent state in the ZnS host lattice. The absorption bands of all QDs were located around 325 nm (3.81 eV) and were higher than that of the bulk ZnS band gap (3.67 eV), consistent with the quantum confinement effect. The photoluminescence spectra of the terbium-doped samples displayed five emission peaks at 467 nm ( 5 D4 → 7 F3 ), 491 nm ( 5 D4 → 7 F6 ), 460 nm ( 5 D4 – 7 F5 ), 484 nm ( 5 D4 – 7 F4 ), and 530 nm ( 5 D4 – 7 F3 ), respectively. The terbium-doped QDs exhibited a higher photocatalytic activity during the degradation of crystal violet dye under UV-light illumination compared to the undoped ZnS QDs. These interesting properties of terbium-doped ZnS QDs are potentially useful for both luminescent and photocatalysis applications.